Mesosignum weddellensis sp. nov. (Crustacea: Asellota: Mesosignidae), a new isopod species from the abyssal Weddell Sea, Antarctica - Choudhury, Madhumita; Brandt, Angelika (Zootaxa, 2004)
Mesosignum weddellensis sp. nov. is described from the abyssal Weddell Sea, Antarctica. This is the second record of Mesosignum from the Southern Ocean, the other known species being M. antarcticum Schultz, 1979. Mesosignum brevispinis Birstein, 1963 from the Pacific Ocean is the most similar species. The most significant difference is the length of the seventh pereonite, which is only half as long as the other pereonites in M. brevispinis, while in M. weddellensis it is as long as the other pereonites.